Effect of low-level laser therapy on the membrane induced by the masquelet technique at an orthotopic site in rabbits - Coris, Jeniffer Gabriela Figueroa [UNESP]; Rahal, Sheila Canevese [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Inamassu, Letícia Rocha [UNESP]; de Abreu Sampaio, Alexandre Botelho [UNESP]; Kano, Washington Takashi [UNESP]; Mesquita, Luciane Dos Reis [UNESP]; Junior, José Ivaldo de Siqueira Silva [UNESP] (FapUNIFESP (SciELO), 2021)
Purpose: To evaluate the low-level laser therapy (LLLT) on the membrane induced by the Masquelet technique in rabbits. Methods: Twelve Norfolk rabbits at approximately 3 months of age were used. A 1-cm segmental defect was induced in both radii, which were filled with polymethylmethacrylate cylinder. LLLT was used postoperatively in the bone defect of one of the forelimbs every 48 hours for 15 days. Six rabbits were euthanatized on third and sixth postoperative weeks. Results: In both forelimbs, radiographs showed new bone growth from radius cut ends on the third postoperative week and more advanced stage on the sixth postoperative week. Ultrasound showed induced membrane one week after the surgery. Histologically, there were no significant differences in the semi-quantitative score of inflammation intensity, total number of blood vessels, bone metaplasia, and collagen. The average thicknesses were 2,050.17 and 1,451.96 μm for control membranes and 2,724.26 and 2,081.03 μm for irradiated membranes, respectively, on third and sixth postoperative weeks. Vascular endothelial growth factor A (VEGF-A) and platelet derived growth factor (PDGF) expression were present in the induced membranes of control and irradiated forelimbs, but there was no significant difference. Conclusion: Based on assessment methods, it was not possible to demonstrate the effect of LLLT on the induced membrane.
Keywords: Infrared rays; Low-level light therapy; Orthopedics; Rabbits